Social and cultural communication in early history - Oqlu, Kazimi Parviz Firudin (Technium Social Sciences Journal, 2021)
In ancient times, the process of social communication and exchange of information was not studied by classical historians, or rather, was not in the center of attention. At the beginning of civilization, various questions of people about nature and man, in addition to everyday needs, were discussed in interaction, and in the absence of science, "words and interpretation" formed the basis of communication. The people who proclaimed and interpreted the divine source of the Word became "wise" and soon began to distinguish themselves from others, claiming their superiority. Thus, priests, priests, preachers, monks and dervishes were formed as carriers of divine wisdom. We can assume that first the Logos (word), then the sages who were the carriers of "thoughts" (information), then associations, organizations, and then alliances were formed between them. These unions were to either become religious communities with limited activity, or grow at the expense of state power. Many materials from ancient mythology confirm this "idea". We see that the ancient sages (that is, the bearers of wisdom) were extremely "tolerant." These sages, who are open to new ideas, listen to different ideas, accept them, combine them into a single doctrine, try to understand them when contradictions arise, and thus new concepts arise. Religious doctrines are the result of a "cultural hybrid".